2017
DOI: 10.1038/s41391-017-0021-x
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance use of aspirin or other non-steroidal anti-inflammatory drugs (NSAIDs) and prostate cancer risk

Abstract: Background Aspirin and other non-steroidal anti-inflammatory drugs (NSAIDs) may have a preventive effect against prostate cancer. However, evidence is limited and still controversial, especially considering non-aspirin non-steroidal antiinflammatory drugs (NSAIDs). Methods Swedish nationwide population-based cohort study including all long-term (≥180 days) adult male users of aspirin (n = 419,931) or NSAIDs (n = 223,437) followed from the first dispense date until the first cancer diagnosis, death or 31 Decemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…Preclinical and clinical trials have demonstrated that the administration of certain NSAIDs, such as celecoxib does not produce a therapeutic effect (54,55). However, there are reports stating that chronic aspirin consumption lowered PSA levels in patients by 5-10% at the time of PCa diagnosis, compared with patients that did not take aspirin (25,27,29). To the best of our knowledge, the mechanism by which aspirin decreases PSA levels at the time of diagnosis has not yet been determined, nor has whether that effect is associated with disease progression (56)(57)(58).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Preclinical and clinical trials have demonstrated that the administration of certain NSAIDs, such as celecoxib does not produce a therapeutic effect (54,55). However, there are reports stating that chronic aspirin consumption lowered PSA levels in patients by 5-10% at the time of PCa diagnosis, compared with patients that did not take aspirin (25,27,29). To the best of our knowledge, the mechanism by which aspirin decreases PSA levels at the time of diagnosis has not yet been determined, nor has whether that effect is associated with disease progression (56)(57)(58).…”
Section: Discussionmentioning
confidence: 99%
“…Anti-inflammatory agents are currently being investigated as a treatment option in different types of neoplasia, such as lung, cervix, ovarian, colon and gastric cancer (24). Inflammation is observed in numerous pathologies, and the current available data demonstrate that it is a critical component in the origin, proliferation and dissemination of different types of cancer, including PCa (25). In PCa, there is evidence of inflammation in the processes of DNA damage, tumor progression and tumor expansion.…”
Section: Decreased Biochemical Progression In Patients With Castratiomentioning
confidence: 99%
See 2 more Smart Citations
“…Aspirin was shown to be effective in the precancerous adenomatosis polyposis coli or APC [152] and in terms of adenoma prior to CRC [153]. Effective aspirin use against cancers had been shown in ovarian [154,155], stomach [156][157][158], pancreas [159,160], hepatocellular carcinoma (HCC) [161], breast [162,163], prostate [164][165][166], melanoma [167] and mesothelioma [168]. Furthermore, aspirin seems to be effective in inflammatory diseases such as Alzheimer's [169] as well as in obesity, as morbid obesity increased cancer risk was reduced in those patients taking aspirin [170].…”
Section: Eicosanoidsmentioning
confidence: 99%